Infant crying problems related to maternal depressive and anxiety symptoms during pregnancy: a prospective cohort study - Tabitha Krogh Ölmestig (BMC, 2021)
Abstract Background Infant crying may cause concerns among new parents and is a frequent reason for seeking help from their general practitioner (GP). The etiology of crying problems in infancy is not fully understood, but recent studies have found associations with maternal mental factors. It is well-established that postpartum depression is related to infant crying problems while the influence of maternal mental problems in pregnancy on infant crying is less investigated. We aimed to explore whether maternal depressive symptoms or maternal anxiety during pregnancy were related to crying problems by the newborn child. Methods In this prospective cohort study, 1290 pregnant women and their newborn children were followed throughout pregnancy until 8 weeks postpartum. Depressive symptoms and anxiety symptoms were assessed three times during pregnancy and again 8 weeks postpartum with the Major Depressive Inventory (MDI) and the Anxiety Symptoms Scale (ASS). Eight weeks postpartum the mothers were also asked whether their child cried in a way they found problematic. Multivariable regression was used to assess the association between depressive and anxiety symptoms during pregnancy and crying problems, and to adjust for potential confounders. Results We found statistically significant associations between high scores of depressive symptoms and anxiety symptoms in pregnancy and infant crying problems. Previously reported strong associations postpartum between depressive symptoms, anxiety symptoms and infant crying problems were also observed in the present data. Conclusion These results indicate that mental problems during pregnancy are associated with having a child with crying problems after birth. If more focus is given to maternal mental problems during pregnancy, the healthcare system might be able to detect and help these women, which would be beneficial for both mother and child.